Seabird and seal responses to the physical environment and to spatio-temporal variation in the distribution and abundance of Antarctic krill at South Georgia, with implications for local fisheries management. (12th October 2022) - Trathan, P N; Fielding, S; Warwick-Evans, V; Freer, J; Perry, F
Abstract: We used 22 years of seasonally and spatially consistent monitoring data to explore marine predator–prey numerical response relationships. Specifically, we tested whether indices of offspring performance (e.g. offspring mass near the time of their independence and/or growth rate) from three Antarctic krill-dependent predators, showed positive relationships with estimates of krill density, determined using fishery-independent acoustic surveys undertaken towards the middle of the predator breeding season. Results showed that indices of predator reproductive performance had little relationship with krill density. In most years, average krill densities were higher on-shelf than off-shelf, potentially providing ecological buffering for predators provisioning offspring. Interestingly, positive response relationships were evident between predator offspring mass and the spatial distribution of krill, measured using indices that represent levels of inequality (patchiness) in krill distribution. These relationships were strongest using indices that reflected the off-shelf krill spatial distribution. We found that krill density and predator offspring mass were also both negatively influenced by sea surface temperature and the Southern Annular Mode, indicating that the environment exerts strong control over ecosystem processes. Finally, we consider the relevance of our results to the ecological framework used by managers responsible for setting catch limits for the regional fishery for krill.